Human Papillomavirus–Associated Adenocarcinoma In Situ of the Vestibule. Issue 4 (October 2017) - Talia, Karen L.; Otton, Geoffrey; Garland, Suzanne; Phillips, Samuel; Scurry, James
Abstract : We report a case of human papillomavirus–associated adenocarcinoma in situ of the vestibule.